2016
DOI: 10.4238/gmr.15038464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregnane X receptor polymorphisms on tacrolimus blood concentrations and the resulting adverse reactions in kidney transplantation recipients

Abstract: ABSTRACT.We investigated the effect of pregnane X receptor (PXR) polymorphisms on tacrolimus (FK506) blood trough concentrations and the associated adverse reactions in kidney transplantation recipients (KTRs). Polymerase chain reaction (PCR)-restriction fragment length polymorphism was used to detect the genotypes of single nucleotide polymorphism loci in 336 KTRs. The PXR six-base deletion mutation was classified using specific allele PCR, and the FK506 blood trough concentration in the KTRs was measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Although the primary role of tacrolimus in this setting is to prevent GVHD, we were unable to accurately depict the impact of pharmacogenetics or drug exposure on incidence of GVHD because patients received other immunosuppressants such as cyclophosphamide or mycophenolate mofetil post-transplant. Additionally, other genetic polymorphisms (eg, PXR, POR, as well as others) [18,[36][37][38] are not accounted for in this study, which could possibly explain some of the observed variability in i.v. tacrolimus exposure among this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary role of tacrolimus in this setting is to prevent GVHD, we were unable to accurately depict the impact of pharmacogenetics or drug exposure on incidence of GVHD because patients received other immunosuppressants such as cyclophosphamide or mycophenolate mofetil post-transplant. Additionally, other genetic polymorphisms (eg, PXR, POR, as well as others) [18,[36][37][38] are not accounted for in this study, which could possibly explain some of the observed variability in i.v. tacrolimus exposure among this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate single nucleotide polymorphisms (SNPs) were mainly selected from previously reported literature, which may potentially affect tacrolimus pharmacokinetics in solid‐organ transplantation. All SNPs and their respective genes analyzed in this study are listed in Table S1 5,8,16–30 . For genotyping, briefly, a 0.5‐mL blood sample was collected and genomic DNA was extracted from ethylenediaminetetraacetic acid‐anticoagulated peripheral blood samples using a commercially available DNA purification kit (EasyPure Blood Genomic DNA Kit, Transgene Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…All SNPs and their respective genes analyzed in this study are listed in Table S1. 5,8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For genotyping, briefly, a 0.5-mL blood sample was collected and genomic DNA was extracted from ethylenediaminetetraacetic acid-anticoagulated peripheral blood samples using a commercially available DNA purification kit (EasyPure Blood Genomic DNA Kit, Transgene Biotech). All samples with a call rate greater than 95% were genotyped using an Infinium Asian Screening Array-China Health Industry Alliance Bead chip (Illumina, Inc.) according to the Illumina Infinium HTS chip standard operating procedures.…”
Section: Genotypingmentioning
confidence: 99%
“…It has been reported that SXR A7635G, an intronic single nucleotide polymorphism (SNP), is able to increase tacrolimus clearance [24,25]. On the other hand, studies in kidney transplant recipients showed no effect of this SNP on tacrolimus blood concentration [26,27].…”
Section: Introductionmentioning
confidence: 99%